ON-FARM ASSESSMENT OF APPLICATION OF BIO-FERTILIZERS IN POTATO PRODUCTION IN EAST KHASI HILL DISTRICT OF MEGHALAYA - Kumar, Shantanu; Sah, Uma; Gupta, V. K.; Pandey, N. K; Deka, C. K.; Baishya, L. K. (Potato Journal, 2013)
Trials were conducted on farmer’s field during summer season in 2002 and 2003 in high rainfall areas of east Khasi hills, to assess the effect of bio-fertilizers (Azotobactor + Phosphobacterium) application on potato production. The treatment consisted of application of 100% NPK through inorganic sources (T1), 75% NPK through inorganic sources + bio-fertilizers 300 g/ha each of Azotobactor and Phosphobacterium (T2) and 50% NPK through inorganic sources + bio-fertilizers 600 g/ha each of Azotobactor and Phosphobacterium (T3). Tuber yield in T1 and T2 were at par, but significantly more than T3. The cost:benefit ratio in T1 and T2 were same (1:4.2), but more than T3 ( 1: 3.7). Farmers perceived this technology as cost saving, less complex and helpful in obtaining better yield of subsequent vegetabl crops.